ATTITUDE AND PERCEPTION OF TOURISTS TOWARDS ECO-TOURISM: A COMPARATIVE STUDY IN TIRUNELVELI AND KANYAKUMARI DISTRICTS (International Journal of Food and Nutritional Sciences, 2022)
Ecotourism has become the buzzword and need of this hour focusing community development and conservation. The present study was conducted in two tourism places namely Tirunelveli and Kanyakumari Districts of South Tamilnadu State. The study is made to identify the problems and prospects and also to investigate the attitude and perceptions of the tourists towards eco-tourism development. The study was undertaken through a sociological survey research design having 2400 numbers of respondents travelling to these places on a tour programme. It may be a spiritual, enjoyment or any other form of tourism which has attracted the tourists from a distance of 600 kilometers and more. The research study was dependent on both primary and secondary data from which analysis was done to reach the conclusion. Eco tourism is one of the most important aspect of the modern day tourism as people give more preference and priority over the tour of this type. Hence an attempt is made by the researcher to analyze the attitude of the tourists and their perception towards ecotourism. The study also tries to explore the most important aspects of eco tourisms in the tour places that facilitate the tour to be more effective and successful.